The Efficacy of Decreased Ovarian Reserve on in Vitro Fertilization Outcome - Özlem KARA; İdil DURAN (Ahi Evran Medical Journal, 2023)
Purpose: In this study, we aimed to compare the effects of microdose and antagonist regimens on IVF-ICSI outcome.